A standing statue of Ganesha - Temples of India Project Team (Jio Institute, 2024)
To the left of the mukhamandapa (front porch) of the Mahakal Temple, one can observe a standing statue of Ganesha. This depiction shows him with four arms, carrying a kamandalu (water pot), akshmala (rosary), another object and a bowl filled with modaks (a form of sweet with stuffing).